Gridded Datasets for Comparative Analysis of Rainfall Patterns Over Eco-Climatic Zones of Narok County, Kenya - Opole Ombogo; Humphreys Obulinji; Amon Karanja (Advances in Meteorology)
This study investigated the spatiotemporal variability of rainfall in the humid, semiarid and arid ecoclimatic zones of Narok County. It addresses the insufficient understanding of rainfall variability within Narok County due to generalizations in previous research and a lack of detailed statistical analysis and data gaps from inadequate stations. The study aims to provide a precise analysis of spatial and temporal rainfall variations to better inform climate adaptation strategies and local planning. The analysis covered the period 1981–2021 and utilized gridded precipitation reanalysis data version two of Modern-Era Retrospective analysis for Research and Applications (MERRA-2) project and monthly rainfall data (mm) from the Kenya Meteorological Department (KMD) for Narok Meteorological Station (NMS). Various statistical techniques, including Kruskal–Wallis (H) test, Rainfall Anomaly Index (RAI), and trend analysis, were employed to assess rainfall patterns across three ecoclimatic zones within the county. The coefficient of variation (CV) was applied in determining the magnitude of precipitation variation across space and time. Results indicate significant temporal variability in rainfall, with distinct seasonal patterns observed. The study identifies a bimodal distribution of rainfall, with wetter months typically occurring in April and November. Spatially, differences in rainfall intensity and variability were observed across the ecozones, with higher variability in arid zones compared to more humid areas. Additionally, interannual rainfall anomalies revealed fluctuations between extreme dry and wet years. Furthermore, trend analysis suggests a gradual increase in annual rainfall over the study period, particularly in more arid regions, highlighting potential shifts in local climate dynamics. These findings underscore the importance of understanding localized rainfall patterns for effective agricultural planning, resources management and climate adaptation strategies in Narok County and similar agroecological contexts.